Patients' Perceptions of Physical Therapists Addressing Opioid Misuse. Issue 1 (January 2023) - Magel, John; Hartman, Paul; Fritz, Julie M.; Koch, Nicholas N.; Dostal, Hannah; Vollmer, Nicholas; Ferguson, Natalie L.; Tapken, Jennifer; Cohee, Kim; Cochran, Gerald; Gordon, Adam J.
Introduction: In the US, rising numbers of patients who misuse illicit or prescribed opioids provides opportunities for physical therapists (PTs) to be engaged in their care. Prior to this engagement, it is necessary to understand the perceptions of patients who access physical therapy services about their PTs playing such a role. This project examined patients' perceptions of PTs addressing opioid misuse. Methods: We surveyed patients, newly encountering outpatient physical therapy services in a large University-based healthcare setting, via anonymous, web-based survey. Within the survey, questions were rated on a Likert scale (1 = completely disagree to 7 = completely agree) and we evaluated responses of patients who were prescribed opioids versus those who were not. Results: Among 839 respondents, the highest mean score was 6.2 (SD = 1.5) for "It is OK for physical therapists to refer their patients with prescription opioid misuse to a specialist to address the opioid misuse." The lowest mean score was 5.6 (SD = 1.9) for "It is OK for physical therapists to ask their patient why they are misusing prescription opioids." Compared to those with no prescription opioid exposure while attending physical therapy, patients with prescription opioid exposure had lower agreement that it was OK for the physical therapist to refer their patients with opioid misuse to a specialist (β = −.33, 95% CI = −0.63 to −0.03). Conclusions: Patients attending outpatient physical therapy seem to support PTs addressing opioid misuse and there are differences in support based on whether the patients had exposure to opioids.